Molecular Detection and Clinical Management of Microsporum canis in Felines - Ponnusamy, Pothiappan; Murugan, Deepalakshmi; Mounika, Kothapalli; Parthiban, Sivamurthy; Chandran, Jayanthy (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Dermatophytosis, primarily caused by Microsporum canis , is a highly contagious fungal infection in felines with significant zoonotic risk. This study evaluated 12 suspected cases, predominantly Persian cats, exhibiting chronic erythema, crusting, and alopecia. Wood’s lamp examination and direct microscopy provided preliminary evidence and PCR confirmed M. canis in five cases by yielding a specific 176 bp amplicon. Positive cats were managed using a multimodal treatment regimen consisting of oral itraconazole pulse therapy (5-10 mg/ kg, week-on/week-off ) combined with topical antifungal shampoos and lime sulfur solutions. By the fourth week of treatment, all cats demonstrated significant clinical recovery, including the resolution of lesions and visible hair regrowth. These findings highlight that PCR offers a highly sensitive and specific diagnostic approach. The findings underscore that PCR-based molecular diagnostics provide a highly sensitive and specific approach for diagnosing M. canis . Early molecular detection combined with targeted systemic and topical antifungal therapy is highly effective in managing feline dermatophytosis and mitigating zoonotic transmission risks.
Keywords: Cats; Dermatophytosis; Itraconazole; Microsporum canis; PCR